Resistance to immune checkpoint inhibitors in gastric cancer - Liu, Kai; Yuan, Shiman; Wang, Chenyu; Zhu, Hong (Frontiers in Pharmacology, 2023)
Gastric cancer (GC) is one of the most common gastrointestinal malignancies worldwide. In the past decade, with the development of early diagnostic techniques, a clear decline in GC incidence has been observed, but its mortality remains high. The emergence of new immunotherapies such as immune checkpoint inhibitors (ICIs) has changed the treatment of GC patients to some extent. However, only a small number of patients with advanced GC have a durable response to ICI treatment, and the efficacy of ICIs is very limited. Existing studies have shown that the failure of immunotherapy is mainly related to the development of ICI resistance in patients, but the understanding of the resistance mechanism is still insufficient. Therefore, clarifying the mechanism of GC immune resistance is critical to improve its treatment and clinical benefit. In this review, we focus on summarizing the mechanisms of primary or acquired resistance to ICI immunotherapy in GC from both internal and external aspects of the tumor. At the same time, we also briefly discuss some other possible resistance mechanisms in light of current studies.